(untitled) (Research, Society and Development, 2021)
The objective was to reflect on the strategies used by nurses to control the anxiety of family members in the preoperative period of pediatric cardiac surgeries. The design adopted was an integrative review, whose search period occurred between the months of August-October/2020 for articles indexed from 2010 on in databases. Sixteen articles were selected for this investigation, and the synthesis of knowledge is presented in two categories: 1) Multiprofessional and interdisciplinary assistance in addressing congenital heart diseases - portrayed assistance with a multidimensional and team approach to heart diseases and 2) Prevention actions and anxiety control of family members performed in the preoperative phase of congenital heart disease as a strategy in nursing care - addressed the nursing actions aimed at controlling anxiety. Communication and reception strategies with sensitive, humanized and qualified listening must be permeated by educational health actions in favor of promoting well-being and controlling anxiety based on the acceptance of the disease, the child’s limitations, as well as the forms of treatment adopted. They are fundamental parts in the therapeutic relationship of the nurse/child/family triad and are configured as important structuring axes in the planning of nursing care.